Teaching experience towards student mistreatment in the COVID-19 pandemic context (2022)
The mistreatment towards the teachers is an incipient phenomenonkwon internationally, it gets relevant to start investigative approaches about thisin Colombia. The results of the research Experiencias docentes ante maltrato de losestudiantes en Bogotá, made in the pandemic context, are presented, the findingscorrespond to situations that take place during the isolation period. There’ve beenmade semi-structured interviews to twenty teachers, the contents analysis allowedto identify the mistreatment forms and their incidence regarding the social link,the process of integration to school life, the hindering in the pedagogic strategiesdevelopment and the manifestation of discomfort.There’ve been known various subjective positionings of the participantteachers, from evasive postures to proactive attitudes towards the mistreatmentexperienced. The teaching experience provides sense to the practice’s contradictionsfor relaunch the pedagogical process in an educational relationship based on respectand the transmission of an interest in learning in the student. The problem of mistreatment of teachers is interpreted from the sociology of social experience, which states that the answers from the roles and functions are insufficient to address a chaotic and incoherent daily world, so the subject must assume the construction of his experience to give a sense of unity and a horizon to guide his social action, in the case of teachers, their educational acts. A flexible qualitative design was assumed, carrying out 20 semi-structured interviews with teachers from public schools in Bogota, these were recorded and transcribed in their entirety, then a content analysis was made identifying forms of mistreatment and its incidence at the level of the social bond and processes of integration to the school culture, the hindrance in the development of pedagogical strategies and manifestations of the subjectivation of the teachers in front of them, having as conceptual references the contributions of François Dubet. At the beginning of the research, the pandemic occurred, making visible forms of mistreatment that were previously simple anecdotes, or were mostly dismissed, which led to the recognition of emotional and behavioral affectations. As a result, an active positioning of teachers in the face of situations of mistreatment was recognized; their work is not limited to the fulfillment of roles and functions, forms of teaching experience were defined that give a sense to the contradictions of practice in order to guide the educational process of their students, specifically the definition of two possible responses was observed, some attached to compliance with current regulations and others from the development of pedagogical innovations.